Enhancing the awareness of emotions through art and drama among crisis-affected Syrian refugee children in southeast Turkey - Necile S Gurle (Intervention Journal of Mental Health and Psychosocial Support in Conflict Affected Areas, 2018)
By learning to identify feelings and express emotions, children can better cope with the difficulties they face, as well as increase their personal resilience. As the Syrian crisis has entered its seventh year, it has had a negative effect on vulnerable populations, especially children. It should be noted that while not all children have been traumatised, many have experienced conflict and crisis, and in turn face challenges expressing and regulating their emotions and behaviour. The aim of the small study, described in this field report, is to explore the power of using drama and art as tools for Syrian children to help them learn to identify their emotions. The qualitative study was conducted at an informal education centre in southeast Turkey, with 10 children, over the course of five workshops. Basic drama and creative art skills were used to raise awareness about emotions as the first phase of emotion regulation.